HEXA-018, a Novel Inducer of Autophagy, Rescues TDP-43 Toxicity in Neuronal Cells - Lee, Shinrye; Jo, Myungjin; Lee, Hye Eun; Jeon, Yu-Mi; Kim, Seyeon; Kwon, Younghwi; Woo, Junghwa; Han, Shin; Mun, Ji Young; Kim, Hyung-Jun (Frontiers in Pharmacology, 2021)
The autophagy-lysosomal pathway (ALP) is an essential cellular mechanism that degrades aggregated proteins and damaged cellular components to maintain cellular homeostasis. Here, we identified HEXA-018, a novel compound containing a catechol derivative structure, as a novel inducer of autophagy. HEXA-018 increased the LC3-I/II ratio, which indicates activation of autophagy. Consistent with this result, HEXA-018 effectively increased the numbers of autophagosomes and autolysosomes in neuronal cells. We also found that the activation of autophagy by HEXA-018 is mediated by the AMPK-ULK1 pathway in an mTOR-independent manner. We further showed that ubiquitin proteasome system (UPS) impairment- or oxidative stress-induced neurotoxicity was significantly reduced by HEXA-018 treatment. Moreover, oxidative stress-induced mitochondrial dysfunction was strongly ameliorated by HEXA-018 treatment. In addition, we investigated the efficacy of HEXA-018 in models of TDP-43 proteinopathy. HEXA-018 treatment mitigated TDP-43 toxicity in cultured neuronal cell lines and Drosophila. Our data indicate that HEXA-018 could be a new drug candidate for TDP-43-associated neurodegenerative diseases.